2021
DOI: 10.1371/journal.pone.0244529
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and practices of open data, preprinting, and peer-review—A cross sectional study on Croatian scientists

Abstract: Attitudes towards open peer review, open data and use of preprints influence scientists’ engagement with those practices. Yet there is a lack of validated questionnaires that measure these attitudes. The goal of our study was to construct and validate such a questionnaire and use it to assess attitudes of Croatian scientists. We first developed a 21-item questionnaire called Attitudes towards Open data sharing, preprinting, and peer-review (ATOPP), which had a reliable four-factor structure, and measured attit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Furthermore, year when the survey is conducted, wording differences, use of scales versus single questions to assess attitudes, as well as differences in collected sociodemographic data that might be explored as explanatory variables, often don't allow direct comparisons. 16 Nevertheless, a survey of 1,015 authors of observational studies, also conducted in 2018, showed that 63% of respondents used reporting guidelines, and that their attitudes towards, awareness, and use of reporting guidelines are in uenced by journals' endorsements, 17 which was also echoed in earlier studies. 18 Our previous analysis of journals' endorsements, however, showed that only 13% of journals across disciplines recommended the use of reporting guidelines, and only 2% required it.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, year when the survey is conducted, wording differences, use of scales versus single questions to assess attitudes, as well as differences in collected sociodemographic data that might be explored as explanatory variables, often don't allow direct comparisons. 16 Nevertheless, a survey of 1,015 authors of observational studies, also conducted in 2018, showed that 63% of respondents used reporting guidelines, and that their attitudes towards, awareness, and use of reporting guidelines are in uenced by journals' endorsements, 17 which was also echoed in earlier studies. 18 Our previous analysis of journals' endorsements, however, showed that only 13% of journals across disciplines recommended the use of reporting guidelines, and only 2% required it.…”
Section: Discussionmentioning
confidence: 91%
“…The framework can also be viewed within the overall research landscape in Africa as to whether the correct policies, incentives and infrastructures exist to enable positive attitudes toward the advancement of science on the continent and globally. The study on attitudes toward data sharing in Africa can also be viewed in the context of the conclusions from Baždarić et al (2021) that this has to be framed within the broader understanding and appreciation of the principles and practices of Open Science. Kim and Adler (2015) explored data-sharing behaviors on individual motivations, institutional pressures, and pressures using a combination of new institutional theory and the theory of planned behavior to develop a model that explains and predicts data sharing behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Meta-research has identified the extent to which researchers engage with Open Research across different disciplines (Cashin et al, 2021;Christensen et al, 2019;Hardwicke et al, 2021;Norris et al, 2021Wallach et al, 2018). There have also been various questionnaire measures developed to assess Open Research behaviours within countries (Baždarić et al, 2021;Pardo Martínez & Poveda, 2018), specific disciplines (Abele-Brehm et al, 2019;Bakker et al, 2022;Bowman et al, 2021;Houtkoop et al, 2018), institutions (University of Glasgow, 2021) or academic status groups (Toribio-Flórez et al, 2021). However, there is no openly available, brief and standardised questionnaire to assess awareness, uptake, and support of Open Research behaviours within and across institutions and countries.…”
Section: Measures Of Open Researchmentioning
confidence: 99%